MORAL VALUE IN THE PATRIOT MOVIE AND RELATION WITH 18th CENTURY - Muhammad Ramdhan; Tenny Sudjatnika; Hasbi Assiddiqi (CALL, 2022)
Movie is one of the media that has a significant impact on the dissemination of information and the transmission of messages to readers or the general public. This study aimed to discover moral value in "The Patriot" movie. This study aimed to discover how moral principles in the movie compare to those in the 18th century. This study also used a qualitative approach to acquire subjective evaluations by utilizing data sources, data collection techniques, data analysis techniques, and time and location. The primary data source was the movie "The Patriot," while secondary sources included the literature on moral issues, particularly the negative repercussions of the industrial revolution. According to the study, the movie "The Patriot" upholds moral principles such as respect, responsibility, fairness, tolerance, wisdom, helping one another, compassion, cooperation, courage, and self-assurance. The investigation came to the conclusion that there was a connection between the moral principles in the film The Patriot and the social circumstances of 18th-century British society. Keywords: social condition, moral values, movie